The Effect of Traction before Closed Reduction in Patients with Developmental Dysplasia of the Hip - Sanjiv S. G. Gangaram-Panday; Suzanne de Vos-Jakobs; Max Reijman (MDPI AG, 2022)
Developmental dysplasia of the hip (DDH) with a dislocated hip can be treated with traction before closed reduction (CR). Currently, there is insufficient evidence supporting the use of preoperative traction treatment for a successful CR. The objective of this study was to determine the effect of preoperative traction on the success rate of primary CR in DDH patients with dislocated hips. A retrospective pair-matched study was performed in DDH patients with dislocated hips. Patients with preoperative traction treatment prior to primary CR were matched (based on age and the severity of DDH on the radiograph) to patients without preoperative traction treatment. The primary outcome was the presence or absence of maintained reduction after three weeks. A match was found for 37 hips, which resulted in the inclusion of 74 hips. No significant difference was found in the number of successful reductions after three weeks between the traction group and the control group (31 vs. 33 hips, p = 0.496). Traction treatment did not significantly improve the short-term or mid-term outcomes for closed reduction. Based on these results, we suggest that traction treatment should not be used as standard care for dislocated hips in DDH.